Analysis of near cortex versus both cortex screw fixation in bone fracture surgery - Ong, Chin Kuan. (2013)
Fractures are commonly encountered injuries due to falls and accidents in humans. A method of stabilizing a fracture is the usage of Locking Compression Plates (LCPs). Accelerated healing is achieved through critical compressive stresses exerted by the bone-plate secured with screws. Prompt healing can occur when the blood supply to bone is maintained or restored early.